KAJIAN RISIKO LINGKUNGAN UNTUK PENGGUNAAN AGEN HAYATI DI BIDANG PERTANIAN - Dwi Andreas Santosa (Jurnal Ilmu Tanah dan Lingkungan, 2019)
In Indonesia, the biological agents have been widely used in the agriculture for reducing chemical fertilizers uses, for controlling plant pest and pathogens, and for increasing rate of composting process. The application of biological agents is especially important in the organic agriculture practices. The agents consist of microorganisms both fungi and bacteria, and in some extent are also viruses, that part of them are imported from other countries. Based on their characteristics, any biological agents that are released into the environment can pose potential problems to the environment or the ecology.  There is a Ministerial Decree that require an environmental risk assessment (ERA) for getting a permission of an importation of biological agents. Unfortunately, there is not any guidance to conduct ERA of biological agents. This paper reviews ERA and using of the approach to do a risk assessment of biological agents that will be used in agriculture.